Evaluation of complete profile and outcome of gunshot injuries in tertiary care centre - Malik, Fazle Rab; Singh, Santosh Kumar; Madeshiya, Shivam; Khan, Roshni; Rai, Nandan (International Surgery Journal, 2019)
Background: Gunshot injuries are range from minor superficial pellet injuries to devastating soft tissue and visceral injuries. The objective of study was to evaluate complete profile and outcome of gunshot injuries in tertiary care centre. Methods: This study was a prospective study. All gunshot injury patients who admitted in Department of Surgery, Moti Lal Nehru Medical College, Allahabad were included in study. Results: Result were analysed in terms of age, sex, rural-urban and religion wise distribution, etiology of injury, arms and ammunition, time elapsed in first aid, site of injury, associated injury, organ involved, Glasgow coma scale, injury severity score, revised trauma score, various blood and radiological investigations, treatment and complications. Conclusions: Gunshot injury was common in male patients, age group 21-30years, Hindu community and in rural areas. Most patients received injury by shotgun. Assault was most common cause followed by accidental injury. Majority of patients had Glasgow coma scale between 13-15, injury severity score below 20 and revised trauma score more than eight. Mortality and morbidity were more common in patients with high injury severity score, low revised trauma score and Glasgow coma scale below 8. Abdomen was most common site involved in gunshot injury. Most of the patients were managed conservatively as these patients had external body surface injury. Laparotomy was done for intra-abdominal injury. Wound infection was the most common complication.